2006
DOI: 10.5558/tfc82819-6
|View full text |Cite
|
Sign up to set email alerts
|

Linking juvenile growth of white spruce with site index

Abstract: The goal of this study was to link the growth of juvenile white spruce stands with an estimate of their site index. We applied a previously developed technique for correcting the height bias created by dominance switching among juvenile trees before trees reached the site index base age (50 years at breast height), using stem analysis data of white spruce from five mixedwood stands in central Alberta. For white spruce of approximately 15 years total age, we found the height of the current top height trees was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Also, care must be taken when determining plot size since it can affect estimates of top height and corresponding estimates of site index (Garcia, 1998, Magnussen, 1999. Another potential problem is that the status of dominants may change over time, a phenomenon associated with the concept of rise and fall in social ranking (Assmann, 1970) or dominance switching (Feng et al, 2006). The latter observation raises the question of stability of dominance and mortality rates of top height trees in a forest stand in relation with site quality estimates, although this may be true for average site trees as well (e.g.…”
Section: Introductionmentioning
confidence: 85%
“…Also, care must be taken when determining plot size since it can affect estimates of top height and corresponding estimates of site index (Garcia, 1998, Magnussen, 1999. Another potential problem is that the status of dominants may change over time, a phenomenon associated with the concept of rise and fall in social ranking (Assmann, 1970) or dominance switching (Feng et al, 2006). The latter observation raises the question of stability of dominance and mortality rates of top height trees in a forest stand in relation with site quality estimates, although this may be true for average site trees as well (e.g.…”
Section: Introductionmentioning
confidence: 85%
“…Moreover, in 15-year-old white spruce stands Feng et al [50] found that the height of the current top height trees was approximately 14% greater than the height of the top trees that would be selected to calculate site index at breast height age 50. These findings also suggest a Type 1 growth response for white spruce [17].…”
Section: Discussionmentioning
confidence: 99%
“…6 and 7 indicate, site index is the major determinant of yield at maturity. Methods to obtain near-unbiased estimates of site index from regeneration survey data have been developed (Feng et al 2006); these estimates are based on recovering the height of top trees (Magnussen and Penner 1996).…”
Section: Future Workmentioning
confidence: 99%